Persepsi Wisatawan terhadap Sapta Pesona Objek Wisata Sejarah Istana Siak Assherayah Hasyimiah Provinsi Riau - Tia Pangestika; Dasrizal Dasrizal; Rika Despica (Departement of Mathematics Education, 2024)
This research aims to determine 1) tourists' perceptions regarding the historical tourist attraction of the Siak Assherayah Palace, Riau Province, 2) the implementation of the sapta charm carried out by managers at the historical tourist attraction of the Siak Assherayah Hasyimiah Palace, Riau Province. This type of research is Quantitative Descriptive using Accidental Sampling, a data collection technique that describes observations and documentation of research results in the field and tourists' perceptions of the historical tourist attraction Siak Assherayah Hasyimiah Palace, Riau Province.The research results are: 1) Tourists' perceptions of Sapta Pesona consisting of something to see, something to do, and something to buy at the Siak Palace tourist attraction produce an average score of